2018
DOI: 10.3390/en11061419
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Fractal-Based Model for Soil-Water Characteristic Curves Incorporating Effects of Initial Void Ratios

Abstract: Abstract:In this paper, a simple and efficient fractal-based approach is presented for capturing the effects of initial void ratio on the soil-water characteristic curve (SWCC) in a deformable unsaturated soil. In terms of testing results, the SWCCs (expressed by gravimetric water content) of the unsaturated soils at different initial void ratios were found to be mainly controlled by the air-entry value (ψ a ), while the fractal dimension (D) could be assumed to be constant. As a result, in contrast to the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Note that, for determining the fractal dimension D, only the test data in the range of ψ a can be adopted, as highlighted in the literature. 34…”
Section: G Tao Et Almentioning
confidence: 99%
“…Note that, for determining the fractal dimension D, only the test data in the range of ψ a can be adopted, as highlighted in the literature. 34…”
Section: G Tao Et Almentioning
confidence: 99%
“…By plotting the ln θ against −ln ψ, the fractal dimension can be calculated by D = 3 − k, in which k is the gradient of the graph. Note that the fractal dimension is seen as a constant for the same soil with different initial void ratios [53].…”
Section: Estimation Of Unsaturated Hydraulic Conductivitymentioning
confidence: 99%
“…It is worth noting that the model presented in this paper is different from that proposed by Zhou et al [51]. In this paper, only one fractal dimension is used to describe the pore distribution characteristics, the air-entry value is directly predicted by the air-entry value model proposed by Tao et al [53], and a fractal model of relative hydraulic conductivity is derived by using the Tao-Kong model (Tao et al [54] indicated that the Tao-Kong model yields good predictions against measured data when the fractal dimension is large, while the predictions of the Mualem model agree well with the measured results of the relative hydraulic conductivity when the fractal dimension is relatively small). In contrast with the proposed model in this paper, the computational efforts of Zhou et al [51] are relatively complex.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are a variety of factors that influence the characteristics of frozen-thawed soil. Firstly, the type of soil-which includes moisture content [6][7][8][9] and pore morphology [10,11]-is a critical factor of the soil characteristics. Zhai et al [12] found that, for consecutive freeze-thaw cycles, the proportion of micro-pores and mini-pores gradually decreased, while that of meso-pores and macropores increased.…”
Section: Introductionmentioning
confidence: 99%